Reflexões sobre o herói na literatura brasileira contemporânea: uma análise do romance O Cheiro do Ralo, de Lourenço Mutarelli - Santos, Renata Oliveira dos (2014)
Exploring the crossroads between different artistic languages and influenced by authors such as Dostoevsky, Kafka, Paul Auster, James Ellroy, Kurt Vonnegut, Ferréz, Valêncio Xavier and Glauco Matoso (some of these are mentioned in O cheiro do ralo) Lourenço Mutarelli emerges in the Brazilian literature of the XXI century producing works that, rather than provoke admiration and delight, provoke unease and estrangement. His novels generally have a hybrid language, inherited from his production as an author of comics, as an actor and as a dramatist, and it is deeply marked by oraliture, by references and reverence to his favorite authors, by pop and popular culture, by crime and eschatology and, most of all, by the urban settings. His characters, noticeable by their alienation, their lack of sense for the existence, reflect a reality that is increasingly common in contemporary life: fragmented, disillusioned, disoriented and frustrated people; men who, unable to cope with their own feelings, close themselves in a psychological universe grounded in dark and unhealthy individualism; narrators who sometimes lurk, as we see in Nada me faltará, or reveal their most intimate thoughts, as in O cheiro do ralo; heroes who, instead of virtues, have only vices. In our research, seeking to uncover the settings of contemporary hero in the novel O cheiro do ralo, by Lourenço Mutarelli, we reflect about his idiosyncrasies, as well as how this hero is portrayed and what kind of human being he is. We wonder: Can we call the unnamed protagonist of O cheiro do ralo a hero? If so or if not, why? How does the characterization of this hero happens? What kind of man the narrative paints? What traits (behaviors, preferences, values) show signs of the various constitutive dimensions of the supposed hero? In order to think about these questions we develop a bibliographical research based on qualitative-interpretative assumptions, in which, initially, we discuss the novel as a literary genre (based on authors like Lucáks, Maingueneau and Watt) and the concept of hero we use (by Campbell, Jung and Meletínski). In chapters two and three, we undertook a detailed analysis of the narrative, emphasizing the most significant moments of the characterization of the hero. In the last chapter, these characteristics were observed through the concepts of perversion (by Freud) and of individualism, inspired by the discussion about the contemporary times prompted by Agamben.